WHERE I COME FROM: TOWARDS A SITUATED-TRANSMUTING CAMIARE WHERE I COME FROM: COMECHINGÓN ETHNOGRAPHY - Misetich Astrada, Laura (Instituto Regional de Planeamiento y Hábitat (RPHA), Unidad Doble dependencia CONICET y UNSJ, 2023)
Where I come from is a short essay that transposes and intersects worlds of reflexivities and problematizations that circulate and exhale, notions and experiences in which readings by mestizo feminist authors such as Gloria Anzaldúa resonate with the purpose of building an aesthetic-political harmony to think about a Comechingón changing ethnography. From an enunciation as a Camiare Comechingona woman by profession an anthropologist, I propose a dialogue open to many worlds from the edges and intersections, reflexively evoking experiences and visions of worlds from situated ethnographies of my family memories. As part of the Camiare Comechingón people and in a con- text of activation of communalization processes and anti-extracivist territorial struggles in the Province of Córdoba in Central-Western Argentina, I invite you to cross, move, recognize, uninstall, transpose borders, epistemological and ontological, to problematize the modern-colonial and patriarchal continuities by which Indigenous women, activists and researchers, were marked.